2019
DOI: 10.1044/2019_aja-ind50-18-0103
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Opinion of Personal Sound Amplification Products: A Preliminary Sentiment Analysis

Abstract: Purpose The purpose of this study was to preliminarily investigate the sentiments associated with consumer opinions of personal sound amplification products (PSAPs). Method Online reviews of 21 popular PSAPs were collected from the Amazon.com website. The reviews for each product were exported to compile individual product-specific text files. A sentiment mining analysis was completed to aggregate the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The less expensive PSAPs with plain features were not as satisfying as the mid- to high-price PSAPs with multifunctional features. 64 However, we believe that unfavoured PSAPs will be eliminated or forced to provide better functions under market pressure. In the foreseeable future, the quality of PSAPs should gradually improve and provide a better alternative for hearing devices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The less expensive PSAPs with plain features were not as satisfying as the mid- to high-price PSAPs with multifunctional features. 64 However, we believe that unfavoured PSAPs will be eliminated or forced to provide better functions under market pressure. In the foreseeable future, the quality of PSAPs should gradually improve and provide a better alternative for hearing devices.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that different PSAPs show a great diversity in price and incorporated functions. 19 , 63 Inconsistent quality of PSAPs is also reflected in the user experience. The less expensive PSAPs with plain features were not as satisfying as the mid- to high-price PSAPs with multifunctional features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PSAPs are gaining popularity, their appreciation and benefits on hearing ability are still equivocal. In a study of customer opinions, the authors identified many customers’ negative impressions across all types of PSAPs studied, with more positive comments expressed about high and medium-cost products than about low-cost products [ 18 ]. This suggests that high and medium-cost products could be more effective than low-cost products.…”
Section: Introductionmentioning
confidence: 99%
“…In the simulated REMs, one basic and two high-end PSAPs showed appropriate levels for three common hearing loss configurations. Additionally, a study explored Amazon customers’ opinions of PSAPs, and the positive reviews showed that there was a strong correlation with the price of the product, demonstrating that PSAPs are also subject to financial influence [ 8 ].…”
mentioning
confidence: 99%